Seasonality of isotopic and chemical composition of snowpack in the vicinity of Jang Bogo Station, East Antarctica - Hur, Soon Do; Chung, Jiwoong; Namgerel, Yalalt; Lee, Jeonghoon (Polish Polar Research, 2021)
Seasonal variations of the isotopic and chemical compositions of snowpits can provide useful tools for dating the age of the snowpit and examining the sources of aerosol. Based on the seasonal layers with δD and δ18O maxima and minima, it was determined that the snowpit, conducted in the vicinity of the Jang Bogo Station in Antarctica, contained snow deposited over a three-year period (2008–2010). Distinct seasonal variations of stable water isotopes were observed, with a slope of 8.2 from the linear isotopic relationship between oxygen and hydrogen, which indicates that the snow accumulated during three years without a significant post-depositional process. The positive correlations (r > 0.85) between Na+ and other ions in the winter period and the positive relationship with the concentrations of the methanesulphonic acid (MSA) and non-sea salt sulfate (nssSO42–) in the warm period (r = 0.6, spring to summer) indicate the significant contributions of an oceanic source to the snowpit. Based on principal component analysis, the isotopic and chemical variables were classified into species representing input of sea-salt aerosol and suggesting potential seasonal markers. This study will support further investigations using ice cores in this region.